Overtourism in Iceland: Fantasy or Reality? - Sæthórsdóttir AD; Hall CM; Wendt M (MDPI (Basel, Switzerland), 2020)
Iceland has been one of the main destinations that have been incorporated into the discourse of overtourism. However, Iceland is different to many other supposed overtourism destinations in that its tourism is based on natural areas. Nevertheless, destination discourses can play an important part in influencing tourist decision-making and government and industry policy making. A media analysis was conducted of 507 online media articles on overtourism in Iceland that were published in 2018, with the main themes being identified via content analysis. The results indicated that the media discourse represented only a partial picture of overtourism and the crowding phenomenon in Iceland, with mechanisms to respond to crowding, the satisfaction level of tourists with their Icelandic nature experience, and local people's support for tourism being underreported. Some of the findings reflect that of other media analyses. However, there are considerable discontinuities between media representations and discourses of overtourism in Iceland, which highlight the importance of national-or destination-level media analysis. The media analysis illustrates the need for a better understanding of different destination discourses and their influence.
Keywords: overtourism; crowding; carrying capacity; commons; Iceland; media; discourse; destination change